The balance between proinflammatory, “bad”, and immunomodulatory, “good”, lipopolysaccharide for understanding gut-derived systemic inflammation - Tume, Rafael; El Sherbiny, Samar; Bono, Roberto; Gautier, Thomas; Pais de Barros, Jean Paul; Meroño, Tomás (Frontiers in Immunology, 2025)
Lipopolysaccharide (LPS) from Gram-negative bacteria has been one of the most studied pathogen-associated molecular patterns triggering rapid inflammatory reactions. However, evidence shows that not all LPS molecules are proinflammatory (“bad”), and that “good” LPS from gut commensal bacteria exert immunomodulatory actions. The Limulus amebocyte lysis test commonly used to quantify LPS in circulation, only targets “bad” LPS, when not inactivated by plasma components. Use of other methods showed healthy subjects featuring elevated levels of LPS (suggesting predominance of “good” or inactive LPS in circulation). This review aims to summarize the evidence supporting the higher abundance of “good” LPS coming from gut commensals of healthy individuals and their potential impact in human health.